Three Dimensional Cube - Gothwal, Pushpa; Singh Shekhawa, Sandesh (International Journal of Engineering and Technology, 2018)
Three dimensional cube is the 3D display device implemented using RGB LED. The objective of this paper to design a 3D CUBE using shift registers controlled by the microcontroller. It consists of using a 8-bit microcontrollers (Arduino Mega 2560, Arduino Uno and AT89s52) with on chip ADC, PWM and UART, RGB LEDs, pulse sensor (SEN-11574), shift registers (74HC595N) as core element of the system. It has six keys used for selecting the defined patterns like square, cube, heart traingle etc.. The application of this project is used for entertainment, display the measured physiological parameter (Heart beat), learning and teaching purpose. It can also help to medical professionals for teaching purpose, defence personals in RADAR and architects.Â Â